pH variations during recovery after the maximum physical effort test - Ramos Álvarez, J. J.; del Castillo Campos, M. J.; Ramón Rey, M.; Segura Dorado, J. L.; Bosch Martin, A. (Archivos de medicina del deporte, 2008)
Introduction: The use of the metabolic substrates during the exercise involves extra and intracellular ionic variations which would induce pH changes triggering fatigue. In the present work, we measure the pH, PO2, and PCO2 baseline, and during the recovery after a maximum physical effort test. Material and methods: We studied 26 male soccer players category of child (Table I). Maximum stress test was performed on treadmill with incremental speed and constant slope protocol (2 km/h/2/1%) to reaching maximum cardiorespiratory criteria. pH, PCO2 y PO2 measurements in capillary basal blood are conducted, and on the 1st and 3rd minute of the recovery stage. Statistical study with ANOVA on a 95% signifi cance level (p </=. 0,05) Results: In Table 2 lists the results obtained of the variables we studied. We found statistically signifi cant differences in the pH during the recovery with respect to the basal (p <0,05), with no difference between minutes 1 and 3 of the recovery stage (p>0,05). During recovery, while PCO2 decreased, PO2 signifi cantly increased (p<0,05). The maximum average oxygen intake was 59,13 +/- 5,23 ml/kg/mn Conclusions: During recovery hyperventilation (RQ >1,1) justifi es the PCO2 drop and the PO2 increase. However, the capillary pH remains acid in relation to the basal one. The pH measurements could be useful to assess the recovery times when planning loads on intermittent sports.